Processed bed elevation picks from airborne radar depth sounding across the Dufek Massif, Pensacola Mountains (1998/99 season) ... - Corr, Hugh (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
A British Antarctic Survey Twin Otter and survey team acquired 8,300 line-km of aerogeophysics data during the Austral summer of 1998/99. Gravity and radio-echo data were acquired simultaneously with the magnetic data at a compromise constant barometric height of 2,200 m, which provides a terrain clearance of 100 m over the highest peaks. Two separate surveys were conducted; one at 5 km line spacing (tie lines at 20 km) over and stretching beyond the southern extent of the Forrestal range (main survey), and one at 2 km line spacing (tie lines at 8 km) covering the Dufek Massif (detailed survey). Ashtech Z12 dual frequency GPS receivers were used for survey navigation. Pseudorange data were supplied to a Picodas PNAV navigation interface computer, which was used to guide the pilot along the pre-planned survey lines. The actual flight path was recovered, using carrier-phase, continuous, kinematic GPS processing techniques. All pseudorange navigation data were recorded at 1 Hz on a Picodas PDAS 1000, PC-based ... : Data available here includes bed and surface elevation sampled from a high resolution (100 m) grid of BEDMAP2 (Fretwell et al., 2013) data along DUFEK flight lines, with ice thickness subsequently derived. Basic information on data acquisition and processing is presented in Ferris et al. (2003). Channel description: Basic Channels Name Description Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1 Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984 Radar segy_name Radar_segy file name TraceNum Radar segy trace number PriNum Raw radar time surfPickLoc Location down trace of surface pick bedPickLoc Location down trace of bed elevation pick surfElev Surface elevation bedElev Picked ice bed elevation tIce Ice thickness, derived from bedPickLoc and surfPickLoc. *Projected coordinates (x and y) are in Lambert conic conformal with ...